Intergenerational Waqf Crowdfunding Behavior: Empirical Evidence From Indonesia - Haling, Hasbi; Indarningsih, Nur Aisyah; Siregar, Suci Wulandari; Jasman, Zahra Ramadani (International Journal of Zakat, 2024)
This study investigates the intergenerational waqf crowdfunding behavior under the lens of Theory Planned Behavior (TPB), Technology Acceptance Model (TAM). A total of 205 respondents covering generation X, Y and Z from across Indonesia was sampled and analyzed using Smart PLS. The Measurement Invariance Assessment (MICOM) test was used to analyze whether the Multigroup Analysis (MGA) model was applicable. The results show that in all generations, perceived usefulness, attitude toward use, and subjective norm affect behavioral intention. Perceived usefulness and attitude toward use also affect attitude toward use of waqf crowdfunding behavior. There was no significant difference except for generation Y and Z regarding behavior between generations. Theoretical and practical implications are drawn from the findings.